INVESTIGATION ON THE MOTIVATION OF RURAL PEOPLE TO PARTICIPATE IN WATERSHED MANAGEMENT PROJECTS - Soleiman RASOULIAZAR; Saeid FEALY-NAHAVAND (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The main purpose of this study was to investigate the motivation of rural people to participate in watershed management projects in Mahabad Township. A field survey based on a questionnaire was used as the main instrument in this research. The validity of questionnaire was confirmed by the panel of specialist group of academic member and natural resources experts. The population included in this study consisted of people who lived in Mahabad’s dam catchment. By Cochran's formula 175 people were determined as sample size. The results showed that rural people has an economic and social motivation to participate in watershed management projects. Also the results show that the sharing of income and benefits from watershed management was the most important economic motivation priority and religious belief about doing things by participating for the most important social motivation priority. In this research also the finding shows that a large variety of information sources must be used about watershed design and educational programs related to watershed management from TV and talking to propagators or natural resource experts in the village about watershed design were the important resource to increase awareness of rural people about watershed management.